Pengaruh Kualitas Pelayanan, Harga, dan Kepuasan Pelanggan Terhadap Loyalitas Pelanggan Motor - Wijaya, Felix; Mulyono, Herry; Nanda Utami, Febby; Benediktus Rolando (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
This study aims to determine the effect of service quality, price, and customer satisfaction on customer loyalty at Champion Motor Mayang branch, Jambi city with 168 respondents. Sample collection was carried out by distributing questionnaires with the Accidental sampling technique to 168 customers of the Mayang branch of the Champion Motor who were deemed suitable as a data source. This research is descriptive research with quantitative methods. This study uses Partial Least Square (PLS) analysis tools. The entire analysis was calculated using the smart PLS version 4 program. The result of the study indicates that service quality has a significant effect on customer satisfaction, price has a significant effect on customer satisfaction, customer satisfaction has a significant effect on customer loyalty, service quality has a significant effect on customer loyalty, price has a significant effect on customer loyalty.